Customer Decisions In Choosing Financing Products At Bmt Nu Bondowoso City Branch: Perspective Of Determining Factors - Dwi Ratnasari; Mustofa Mustofa; Muhdar Muhdar (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the relationship between promotional strategies and processes to customer decisions in choosing financing products at BMT NU, Bondowoso City Branch. Data for this study were obtained from distributing questionnaires to research objects. The sampling technique used Simple Random Sampling. This type of research is quantitative research. The sample used in this study was the Customer Bank with a total of 30 respondents. Data analysis used multiple linear regression analysis, determination coefficient test (r2), t test and f test using the SPSS. The results of this study inform that promotional strategies do not significantly affect customer decisions in choosing Lasisma financing. The results of simultaneous test statistics calculations can be concluded that promotions and processes simultaneously affect customer decisions in choosing Lasisma financing. The results of the process strategy test show a significant effect on customer decisions in choosing financing